2020
DOI: 10.1002/da.23084
|View full text |Cite
|
Sign up to set email alerts
|

Prior trauma‐related experiences predict the development of posttraumatic stress disorder after a new traumatic event

Abstract: Background: Many reports have documented the relationship between previous traumatic experiences, including childhood trauma, and the development of later life psychopathology, including posttraumatic stress disorder (PTSD). Identification of individuals at greatest risk for the development of PTSD could lead to preventative interventions. The present study examined the developmental course of PTSD after trauma exposure, using histories of previous traumatic experiences and the severity of the reaction to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…Participants who had family or friends who were infected with SARS or H1N1 scored higher on PTSS subscales and on total PTSS than those without related experiences. These results are consistent with prior studies showing that previous traumatic experience is an important risk factor for PTSS (Gould et al, 2020 ; Ozer et al, 2003 ). It is therefore important for clinicians to be particularly vigilant in attending to those who have experienced previous trauma during psychological intervention.…”
Section: Discussionsupporting
confidence: 93%
“…Participants who had family or friends who were infected with SARS or H1N1 scored higher on PTSS subscales and on total PTSS than those without related experiences. These results are consistent with prior studies showing that previous traumatic experience is an important risk factor for PTSS (Gould et al, 2020 ; Ozer et al, 2003 ). It is therefore important for clinicians to be particularly vigilant in attending to those who have experienced previous trauma during psychological intervention.…”
Section: Discussionsupporting
confidence: 93%
“…According to the Developmental Psychopathology framework [ 35 ], psychopathological difficulties in parents and children are the result of the dynamic interplay between individual and relational protective and risk factors, from individual vulnerabilities to parents’ strengths. Among individual vulnerabilities, some studies have shown that having experienced previous trauma may lead the individual to a greater vulnerability to the effects of subsequent traumatic experiences, with a higher risk of developing post-traumatic stress symptoms [ 36 , 37 , 38 ]. The stress sensitization model posited that an individual who has higher levels of prior trauma exposure might manifest higher sensitivity and lower tolerance to stress when exposed to later stressful life events [ 33 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals become more sensitive to perturbations in their environment, have excessive intrusive thoughts and musings which may trigger a depressive episode. We originally proposed that anxiety and trauma disorders can be thought of increased hyperexcitability in the amygdala and its circuits ( Rosen and Schulkin, 1998 ) and many studies support this idea ( Morgan et al, 1995 ; Lähdepuro et al, 2019 ; Gould et al, 2021 ).…”
Section: Kindling: a Metaphor For Hyperexcitabilitymentioning
confidence: 99%